Computed Tomographic Imaging of 3 Patients With Coronavirus Disease 2019 Pneumonia With Negative Virus Real-time Reverse-Transcription Polymerase Chain Reaction Test. (31st March 2020) - Xu, Junqing; Wu, Ruodai; Huang, Hua; Zheng, Weidong; Ren, Xinling; Wu, Nashan; Ji, Bin; Lv, Yungang; Liu, Yumeng; Mi, Rui
Abstract: We reported computed tomographic (CT) imaging findings of 3 patients with coronavirus disease 2019 (COVID-19) pneumonia with initially negative results before CT examination and finally confirmed positive for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by real-time reverse-transcription polymerase chain reaction assay.